Evaluation of coloring therapy as an anxiety reduction strategy in the older adults in the community area - Putri Noor Rochmah Ida Ayu Trisno; Cahyaningrum Etika Dewi; Wurdaningsih Tri Kusuma; Syangadah Zulfiati; Mesayu Salma Fadzila (BIO Web of Conferences)
The phenomenon of an increasing older adult population requires attention to various health problems, especially mental health issues such as anxiety, which is often overlooked. Anxiety in older adults can significantly impact their quality of life. One promising approach to managing anxiety is art therapy. This study aims to evaluate the effectiveness of art therapy in reducing anxiety in older adults within the community. This research used a pre-experimental design with a one-group pre-post-test model. The sample consisted of 35 participants aged 60 years and older who met the inclusion criteria, namely the ability to use their upper extremities for activities and no physical or mental disorders that would prevent participation in art therapy. Participants were selected through accidental sampling. Participants’ anxiety was measured using the Geriatric Anxiety Scale (GAS), which consists of 25 items, before and after four weeks of intervention. The art therapy intervention was conducted in two sessions per week for four weeks, totaling eight sessions. Each session involved expressive arts activities designed to help participants express themselves and alleviate anxiety. The results of the descriptive analysis showed that 25.7% of participants experienced mild anxiety, 65.7% moderate anxiety, and 8.6% severe anxiety before the intervention. After therapy, analysis using the Wilcoxon test showed a significant reduction in anxiety (p=0.000). This research demonstrates that art therapy is effective in reducing anxiety in older adults. Therefore, art therapy can be integrated as a nonpharmacological intervention that is beneficial in improving the quality of life of older adults and can be applied by health professionals and community workers.